Atypical Hemolytic Uremic Syndrome in a 13-year-old Lao Girl: A Case Report - Philavanh Kedsatha; Hae Il Cheong; Yong Choi (Korean Society of Pediatric Nephrology, 2019)
Atypical hemolytic uremic syndrome (aHUS), a rare form of thrombotic microangiopathy, is distinguished from the typical form by the absence of a preceding verotoxin-producing Escherichia coli infection. Notably, aHUS occurs in association with genetic or acquired disorders causing dysregulation of the alternative complement pathway. Patients with aHUS may show the presence of anti-complement factor H (CFH) autoantibodies. This acquired form of aHUS (anti-CFH-aHUS) primarily affects children aged 9-13 years. We report a case of a 13-year-old Lao girl with clinical features of aHUS (most likely anti-CFH-aHUS). The initial presentation of the patient met the classical clinical triad of thrombotic microangiopathy (microangiopathic hemolytic anemia, thrombocytopenia, and acute kidney injury) without preceding diarrheal illness. Low serum levels of complement 3 and normal levels of complement 4 indicated abnormal activation of the alternative complement pathway. Plasma infusion and high-dose corticosteroid therapy resulted in improvement of the renal function and hematological profile, although the patient subsequently died of infectious complications. This is the first case report that describes aHUS (possibly anti-CFH-aHUS) in Laos.